2003
DOI: 10.1071/sr02128
|View full text |Cite
|
Sign up to set email alerts
|

Estimating a nitrous oxide emission factor for animal urine from some New Zealand pastoral soils

Abstract: The Intergovernmental Panel on Climate Change methodology estimates that over 50% of total nitrous oxide (N 2 O) emissions in New Zealand derive from animal excreta-N deposited during grazing. The emission factor for excreta-N as used by this methodology has an important impact on New Zealand's total N 2 O inventory. The objectives of this study were to refine the N 2 O emission factor for urine by simultaneously measuring N 2 O emissions from 5 pastoral soils of different drainage class, in 3 different region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
125
2
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 214 publications
(137 citation statements)
references
References 31 publications
9
125
2
1
Order By: Relevance
“…A 10-ml headspace air sample was taken from each chamber at 0 (T 0 ) and 60 (T 60 ) min. Previous studies examining emissions from animal excreta on pasture in a similar location found that emission rates were linear over this time period (de Klein et al, 2003;Saggar et al, 2004).…”
Section: Methodsmentioning
confidence: 72%
See 1 more Smart Citation
“…A 10-ml headspace air sample was taken from each chamber at 0 (T 0 ) and 60 (T 60 ) min. Previous studies examining emissions from animal excreta on pasture in a similar location found that emission rates were linear over this time period (de Klein et al, 2003;Saggar et al, 2004).…”
Section: Methodsmentioning
confidence: 72%
“…A 10-ml headspace air sample was taken from each chamber at 0 (T 0 ) and 60 (T 60 ) min. Previous studies examining emissions from animal excreta on pasture in a similar location found that emission rates were linear over this time period (de Klein et al, 2003;Saggar et al, 2004).Following excreta treatment application in early September 2011, N 2 O emission samplings were carried out at least weekly, as described above. More frequent sampling occurred in the first month and following rainfall (van der Weerden et al, 2013).…”
mentioning
confidence: 99%
“…It is suggested that similar studies should be conducted under differing environmental conditions to determine whether the effects hold true. Real urine is generally advocated for the calculation of emission factors (de Klein et al 2003); however, the use of artificial urine was beneficial in the present study as it allowed the manipulation of N concentration. The artificial urine contained the recommended constituents for adequate representations of urine for N 2 O emissions (Kool et al 2006) and the proportion of urea was increased to manipulate the N content, which is consistent with an increase in the proportion of urea excreted by ruminants occurring as a result of increased dietary crude protein (Dijkstra et al 2013).…”
Section: Discussionmentioning
confidence: 83%
“…Low emission factors have been previously observed above sheep-grazed pastures under dry summer months, with maximum emissions occurring under cooler and wetter soil conditions (Allen et al 1996;Saggar et al 2007). Rainfall and soil drainage class have been identified as key variables influencing N 2 O emission factors from urine returns (de Klein et al 2003), and a consideration of environmental and management factors (which are not considered in the IPCC Tier 1 approach) will undoubtedly be important for better constraining N 2 O emission estimates from grazed soils.…”
Section: Discussionmentioning
confidence: 99%
“…Hourly N2O emissions were calculated based on the rate of change in N2O concentration within the chamber during the measurement period and taking into account air temperature, atmospheric pressure, and the ratio of surface area to chamber volume. Hourly N2O flux was used to calculate daily emissions (Blackmer et al 1982;de Klein et al 2003).…”
Section: Usa) Fitted With a 63mentioning
confidence: 99%